VD_FINDINFO HC / 2013 / 30 vom 14. Januar 2013 - VD Tribunal cantonal (2013)
FRAIS D'EXPERTISE, DROIT TRANSITOIRE | 176 CC, 242 al. 1 CPC, 242 CPC, 184 al. 3 CPC (CH), 184 CPC (CH), 319 let. b ch. 1 CPC (CH), 322 al. 1 CPC (CH), 326 al. 1 CPC (CH), 404 al. 1 CPC (CH), 404 CPC (CH)